Perceived control and health-related quality of life in heart transplant recipients. (August 2018) - Doering, Lynn V; Chen, Belinda; Deng, Mario; Mancini, Donna; Kobashigawa, Jon; Hickey, Kathleen
Background: Perceived control has been associated with improved mental health and health-related quality of life (HRQOL) in cardiac populations. However, this concept has not been well-studied in heart transplant groups. Aims: We examine the relationship of perceived control to symptoms of anxiety and depression and HRQOL after transplant. We also examine the extent to which anxiety and depressive symptoms mediate the relationship between perceived control and HRQOL. Methods: Our cross-sectional analysis included 113 adult heart transplant patients from the NEW HEART study. High versus low perceived control groups were determined by median split for chi-square and t -test analyses. Hierarchical multiple linear regression models were used to examine the influence of perceived control on symptoms of depression and anxiety and HRQOL. Mediation analyses included Baron and Kenny's four-step regression approach and Preacher and Hayes' bootstrapping technique to test the indirect effect of perceived control on HRQOL. Results: Heart transplant patients who reported lower perceived control were more likely to be female ( p =0.003), and had significantly more depressive symptoms ( p <0.001) and anxiety ( p <0.001), and lower HRQOL ( p <0.001) than those with higher perceived control. Perceived control was a significant predictor in regression models of depressive and anxiety symptoms and HRQOL. In mediation analyses, depressive and anxiety symptoms mediated the effect of perceived control on HRQOL. Conclusion: Perceived control is associated with improved depressive and anxiety symptoms and HRQOL after transplant. The relationship between perceived control and HRQOL is mediated by depressive and anxiety symptoms. Future interventions should target perceived control to improve overall HRQOL.